Growth, biomass and carbon sequestration performance of fast-growing tree species under high density plantation at Prayagraj and Raebareli - Tomar, Anita; Bijay Kumar Singh (Indian Journal of Agroforestry, 2025)
Comparison in growth of three fast-growing trees, viz. Eucalyptus spp., Casuarina equisetifolia and Gmelina arborea in high-density plantation in two different districts viz. Badanpur (Prayagraj) and Deh (Raebareli) in, Uttar Pradesh, India, with three different spacings, viz., 1×1 m, 1.2×1.2 m and 1.5×1.5 m. Both experiments trials were established in July 2019 and data were recorded after three years. The height maximum found at Badanpur in (T1): Eucalyptus (1×1m) 10.48 m followed by (T7): Eucalyptus (1.5×1.5 m) 9.12 m which was at par with each other whereas in Deh maximum in (T7): Eucalyptus (1.5×1.5 m) 11.77 m followed by (T4): Eucalyptus (1.2×1.2 m) 10.31 m which was also at par with each. The diameter maximum found at Badanpur in (T1): Eucalyptus (1×1m) 8.25 cm followed by (T7): Eucalyptus (1.5×1.5 m) 7.35 cm, (T6): Gmelina (1.25×1.25 m) 7.14 cm, (T4): Eucalyptus (1.2×1.2 m) 7.12 cm, which was also at par to each other whereas in Deh maximum in (T7): Eucalyptus (1.5×1.5 m) 8.37 cm followed by (T4): Eucalyptus (1.2×1.2 m) 6.79 cm. The biomass, Carbon stock and carbon sequestration was maximum found in (T1): Eucalyptus (1×1m) 2033.68, 1016.84 and 3731.80 t ha-1 followed by (T4): Eucalyptus (1.2×1.2 m) 872.17, 436.09 and 1600.44 t ha-1 respectively at Badanpur whereas in Deh maximum was found in (T7): Eucalyptus (1.5×1.5 m) 1040.32, 520.16 and 1908.98 t ha-1 followed by (T4): Eucalyptus (1.2×1.2 m) 941.07, 470.53 and 1726.86 t ha-1 respectively. The volume productive index was maximum found in (T1): Eucalyptus (1×1m) 586.07 m3 ha-1 year-1 followed by (T7): Eucalyptus (1.5×1.5 m) 404.81 m3 ha-1 year-1 whereas biomass was maximum found in (T1): Eucalyptus (1×1m) 677.89 t ha-1 year-1 followed by (T4): Eucalyptus (1.2×1.2 m) 290.74 t ha-1 year-1 at Badanpur. In dah the maximum volume and biomass productive index was maximum found in (T7): Eucalyptus (1.5×1.5 m) 299.83 m3 ha-1 year-1 and 346.81 t ha-1 year-1 followed by (T4): Eucalyptus (1.2×1.2 m) 271.22 m3 ha-1 year-1 and 313.71 t ha-1 year-1 respectively. On the basis of this study, we recommend that Eucalyptus, Casuarina and Gmelina can be planted in degraded and fallow land in 1×1m spacing for maximum volume production per unit area.